STAGES OF FORMATION OF BASIC CONCEPTS OF DISTANCE LEARNING (Education in the 21st Century, 2023)
Short introduction. The article analyzes the historical stages of formation of basic concepts of distance learning (correspondence learning, distance learning). Theoretical aspects of the development of distance education in Ukraine are considered. Based on the analysis of scientific sources, the interpretation of key concepts of distance education and distance learning is systematized. Emphasis is placed on the fact that the modern understanding of the concepts and terms of distance learning is based on its interpretation as activities using Internet technologies and resources. A comparison of distance education and distance learning, related concepts of open education and blended learning is made.Keywords: distance learning; distance education; e-education; blended learning, educational reforms; innovative education; educational programs; national education; establishment of higher education; information-and-communication technologies.